Peace, Conflict and Sustainable Development: Management Implications for Peace Education in Nigeria - Ebire, Matthew Olusola; Akinsolu, Abiodun Olatoun; Odedokun, Ezekiel Adeyemi (NIU Journal of Social Sciences, 2026)
This paper discusses the concepts of Peace, Peace Education and Conflicts and its management implications which always unavoidably rare its head in interrelationships between humans in societies, thereby deterring strong volitions to achieving sustainable development. The paper dwells on the role of peace education as a globally acclaimed measure for achieving sustainable education and to a greater extent, sustainable development. It also highlights the rationale for peace education in Nigeria, while recommendations for achieving sustainable development through peace education were made. Among these, is that peace education should be introduced to teachings and trainings of each age group; teachers; head teachers; public servants and in research institutes both as pre-service and as in-service trainings. The paper also highlighted several management implications on social institutions in Nigeria such as Strategic management, peace building and governance, conflict management and sustainable development goals. Keywords: Peace, Peace education, Conflict, Sustainable education, Sustainable development and Management